(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2021)
As an approach to multilingualism, the study of linguistic landscape (LL) in educational settings is still underexplored. LL study is significant to disclose various aspects of language existence and use. In the school context, it might reveal what and how languages are used among school members and their relevance to education. This article aims to examine the emerging themes of signs’ messages in school LL and the contribution of multimodal social semiotic elements to the signage social meanings. It studied 890 signs from five senior high schools in Yogyakarta, Indonesia and used a geosemiotic approach to analyse the verbal and visual texts. The findings reveal eight major themes of messages: (1) location or place direction, (2) morality and religion, (3) environment and energy, (4) school identity and information, (5) activities, (6) how to comport oneself, (7) science and knowledge and (8) rules, regulations and acts. The three main modes (language, image and colour) in the school LL serve the functions to communicate and to represent the schools’ social reality relevant to the emerging themes through iconic and symbolic semiotic systems. The school LL is a multifaceted social construct that also reveals the relationship between the sign makers and the addressees.